Subepicardial aneurysm with free wall rupture and its successful surgical intervention: a case report. Issue 2 (20th February 2021) - Fukui, Tomoki; Kitabayashi, Katsukiyo; Ogasawara, Nobuyuki; Hasegawa, Shinji
Abstract: Background: Subepicardial aneurysm (SEA) is an uncommon but potentially fatal complication of acute myocardial infarction (MI) associated with an increased risk of free wall rupture (FWR) leading to sudden death. We describe a rare case of a silent myocardial infarction complicated by SEA and subsequent FWR, resulting in cardiac tamponade. Case summary: A 68-year-old man with no previous chest symptoms presented with syncope. Cardiac computed tomography incidentally revealed a small aneurysmal cavity at the inferolateral wall of the left ventricle, which was overlooked on initial transthoracic echocardiography. Coronary angiography demonstrated a narrowed first obtuse marginal branch with coronary slow flow, suggesting that spontaneous recanalization of the occluded obtuse marginal branch induced SEA and subsequent FWR. The patient underwent an emergency left ventricular aneurysm repair. The post-operative course was uneventful, and the patient was discharged from the hospital on post-operative day 20. Discussion: This case emphasizes the importance of prompt detection and surgical intervention for SEA. Subepicardial aneurysm should be suspected in patients with pericardial effusion and suspected MI. Cardiac computed tomography is not only useful in the detection of such cases but also facilitates the development of a successful surgical strategy.